Students' Perceptions Towards Direct and Indirect Feedback in Speaking for Social Purposes - Melly, Sisilia; Listyani, Listyani; Sumakul , Toar Yusak G. (Satya Widya, 2024)
Speaking is one of the most important subjects in learning a foreign language. In speaking class, there are some mistakes that students found, which must be corrected. One way that teachers usually do to help the students cope with their problems is giving feedback. This study was aimed to find out about students’ perceptions towards direct and indirect feedback in Speaking for Social Purpose class. This study was guided by these two questions: What are PBI students’ perceptions towards direct feedback given by the teacher in the Speaking for Social Purposes class? What are PBI students' perceptions towards indirect feedback given by the teacher in the Speaking for Social Purposes class? This research involved 5 fifth-semester and 5 eight-semester students from the English Language Education Program (ELEP), Faculty of Language and Arts (FLA), Universitas Kristen Satya Wacana in Salatiga, Central Java. They were randomly chosen to be the participants for the research sample. A semi-structured interview was used to collect the data. The researchers found that there were several problems faced by students during the Speaking for Social Purposes class. Moreover, it was found that the students recognized teachers’ feedback was very important for their study, especially in speaking because it helped them to know their mistakes or problems and they can correct their mistakes. The direct feedback became the most favorite kind of feedback and was very important for the students.